The impact of extracellular matrix proteins on bovine fibro‐adipogenic progenitor cell adhesion, proliferation, and differentiation in vitro - Perri Gish; Madison Stewart; Brandon Khuu; Nathaniel Meyer; Payam Vahmani; Lucas Smith (Physiological Reports)
Abstract Fibro‐adipogenic progenitor cells (FAPs) are mesenchymal stem cells that produce extracellular matrix (ECM) and intramuscular adipocytes in skeletal muscle. While FAPs have demonstrated responsiveness to their physical environment, there is limited knowledge of how the ECM substrate of FAPs impacts their differentiation, particularly in livestock animals. We hypothesized that the ECM substrate FAPs are cultured on will differentially impact their adherence, proliferation, and differentiation. Through an initial screen of 9 ECM proteins and their combinations, significant variation of bovine FAP attachment and differentiation across coatings was observed. The ECM substrates fibronectin, collagen 6, vitronectin, and a combination of fibronectin and collagen 6 were selected for further testing. Notably, fibronectin increased cell proliferation and attachment rates, without impairing FAP adipogenic or fibrogenic differentiation compared to the other coatings. Benefits of fibronectin were maintained at lower concentrations and when combined with less favorable coatings such as collagen 6. When assessed for their adipogenic potential on each coating at different substrate stiffnesses, lipid accumulation decreased with increasing substrate stiffness, while cell attachment increased on stiffer substrates. Overall, these results demonstrate the high responsiveness of FAPs to their ECM substrate, along with highlighting fibronectin as a preferred substrate for in vitro experiments with bovine FAPs.